Absolute configuration and anti-tumor activity of torrubiellin B. Issue 30 (22nd July 2015) - Pérez Hemphill, Catalina Francis; Daletos, Georgios; Hamacher, Alexandra; Kassack, Matthias Ullrich; Lin, Wenhan; Mándi, Attila; Kurtán, Tibor; Proksch, Peter
Graphical abstract: Highlights: A dimeric anthracene derivative was isolated from the endophyte Acremonium sp. The absolute configuration of torrubiellin B was established by ECD calculations. Torrubiellin B showed strong anti-tumor activity against several cancer cell lines. Abstract: The dimeric anthracene derivative torrubiellin B (1 ) was isolated from the endophytic fungus Acremonium sp. that had been obtained from leaves of the Mangrove plant Sonneratia caseolaris . The absolute configuration of 1 was established as (5′ R, 10′ S, 10a′ R ) for the first time on the basis of its electronic circular dichroism (ECD) spectra aided with TDDFT-ECD calculations. Torrubiellin B (1 ) exhibited strong anti-tumor activity when tested in vitro against several solid cancer cell lines including cells that are resistant against the widely used cytostatic drug cisplatin. The IC50 values of 1 against cisplatin sensitive and cisplatin resistant cells were in the range of 0.2–2.6 μM depending on cell line investigated.